If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + iy)(x + iy) = 2x Reorder the terms: (iy + x)(x + iy) = 2x Reorder the terms: (iy + x)(iy + x) = 2x Multiply (iy + x) * (iy + x) (iy(iy + x) + x(iy + x)) = 2x ((iy * iy + x * iy) + x(iy + x)) = 2x Reorder the terms: ((ixy + i2y2) + x(iy + x)) = 2x ((ixy + i2y2) + x(iy + x)) = 2x (ixy + i2y2 + (iy * x + x * x)) = 2x (ixy + i2y2 + (ixy + x2)) = 2x Reorder the terms: (ixy + ixy + i2y2 + x2) = 2x Combine like terms: ixy + ixy = 2ixy (2ixy + i2y2 + x2) = 2x Solving 2ixy + i2y2 + x2 = 2x Solving for variable 'i'. Reorder the terms: 2ixy + i2y2 + -2x + x2 = 2x + -2x Combine like terms: 2x + -2x = 0 2ixy + i2y2 + -2x + x2 = 0 The solution to this equation could not be determined.
| 22.5+7=(n-3.4) | | -4n+6= | | (x^2+y-z)(y^2+z-x)(z^2+x-y)= | | 5w+-6w-(-2w)=12 | | abs(x-38)=abs(38-x) | | X*(4*x)=121 | | 5y+7x=19-3y | | 2f+10=30 | | 24(x+13)-11=25+292 | | 2q-4q+5+9= | | 25.77=5g+3.72 | | 2x-3x=4x-6-3-5 | | -5c-(-2c)-(-5c)-(-6c)-(-8c)=-20 | | j^2+20j+19=0 | | 7u+3u+u-10u=17 | | 9m+4-2+7m= | | 7(r+7)=5r+5r | | 1=-8+3y | | -19h-10h+13h=16 | | 5(x+2)-17=35 | | 11y+10=15y-10 | | 10(s-7)=-119 | | 3(x-2)-(x+1)=3 | | 10(s-7)=-199 | | z/-23 | | 45x=17 | | 2h-h=9 | | 8x^4-66x^2+58=0 | | 61=-17+7m | | 8(x-9)=-6x-2 | | 7x+6+4x+9= | | 5+1x=30 |